Abdominal Surgical Emergencies in the Puerperium: A Descriptive Study - Bushra Nabi, Asif Mehmood (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Puerperal abdominal surgical emergencies are rare but potentially fatal diseases that are difficult to diagnose and treat. The classical signs of acute abdomen are usually masked by physiological alterations postpartum, which contributes to making the diagnosis late and causing further maternal morbidity. This may be due to both obstetric and non-obstetric factors, but the burden is rising in the number of cesarean sections. Objective: To characterize the spectrum, clinical expression, management plan, and outcome of abdominal surgical emergencies that occur in the puerperium of a tertiary care hospital. Methods: The study was a descriptive retrospective study that was carried out in a Khalifa Gul Nawaz Teaching Hospital Bannu during a period November 2022 to June 2023. The review of the medical records of women who made presentations within six weeks after delivery with abdominal surgical emergencies was done. The descriptive statistics were used to analyze data about demographic features, delivery mode, time of presentation, diagnosis, imaging techniques, surgery, post-operational complications, and maternal outcome. Results: One hundred and thirty-eight puerperal women who had abdominal surgical emergencies were identified. Most of them were multiparous, and had a cesarean birth. Majority of the patients came during the first two weeks after childbirth. The diagnoses were mostly acute appendicitis, then intestinal obstruction and post-cesarean intra-abdominal sepsis. More than three-quarters of cases needed emergency surgical intervention. Minority of patients were found to have postoperative complications with wound infection and paralytic ileus being the most common ones. None of the mothers died. Conclusion: Emergencies of abdominal surgery during the puerperium can be characterized by high morbidity, though good results could be obtained when they are detected early, imaged promptly and surgical intervention is administered. Referral systems and low surgical evaluation threshold are important areas of enhancement that enhance maternal outcomes. Keywords: puerperium; acute abdomen; cesarean section; surgical emergencies.